(3MGTjI Ydi TQM GdQMHjI ddTfThQjs - (3GdNVQj, eMeO Hf eUWai Hf MSf, J (B1287 (3g`s ((3eMeO CHh Mj Gddgs)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdhGQK HYO afG Ndbg CeG HYO ajbhd eMeO GdNVQj GdTGaYj gPg MhGTj Ydi TQM GdTfThQj Ydi GdQMHjIs
(3BNQgG (B:s
(3addCe GdKdK cGedG hddLO GdSOS hde jHb ddCN TjA ajSbW dGSJZQGb GdaQhV hGddg CYdes
(3GdJhKjbGJ GdeQLYjI (B:s
3 / 375
(3agQS GdCRgQjI (B2 / 672s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdaQGFVs